2000
DOI: 10.1152/jappl.2000.89.5.1793
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle metabolic and ionic adaptations during intense exercise following sprint training in humans

Abstract: The effects of sprint training on muscle metabolism and ion regulation during intense exercise remain controversial. We employed a rigorous methodological approach, contrasting these responses during exercise to exhaustion and during identical work before and after training. Seven untrained men undertook 7 wk of sprint training. Subjects cycled to exhaustion at 130% pretraining peak oxygen uptake before (PreExh) and after training (PostExh), as well as performing another posttraining test identical to PreExh (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
142
4
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(175 citation statements)
references
References 35 publications
28
142
4
1
Order By: Relevance
“…Other researchers have also found an increased time to exhaustion after HIT Harmer et al, 2000;. Additionally, HR has been found to be lower at a given work rate during exercise tests to exhaustion after HIT Harmer et al, 2000).…”
Section: B Oxygen Deliverymentioning
confidence: 85%
See 3 more Smart Citations
“…Other researchers have also found an increased time to exhaustion after HIT Harmer et al, 2000;. Additionally, HR has been found to be lower at a given work rate during exercise tests to exhaustion after HIT Harmer et al, 2000).…”
Section: B Oxygen Deliverymentioning
confidence: 85%
“…While studies using a two week six session HIT protocol did not see an increase in maximal oxygen uptake, protocols lasting four to eight weeks did find an increase in maximal oxygen uptake with HIT Harmer et al, 2000;Krustrup et al, 2004;MacDougall et al, 1998;. All of the studies mentioned above trained with cycling exercise but one study using running HIT found no change in maximal oxygen uptake over the course of six weeks of training (Marles et al, 2007).…”
Section: B Oxygen Deliverymentioning
confidence: 98%
See 2 more Smart Citations
“…It should be noted that in our study the ratio of exercise time to pause time was 1 to 12 ±1. Implementation of more work during the first test may be related to an increased volume of blood flowing through the muscles, providing them with significant amounts of oxygen, which can improve lactate transport from the muscles by MCT transporters (Brookes, 1986;Harmer et al, 2000;McKenna et al, 1997). Chmura, Zatoń (2011) suggest that repetition of 90-second efforts might lead to energy from glycolytic processes being used.…”
Section: Discussionmentioning
confidence: 99%